PENGARUH E-SERVQUAL TERHADAP KEPERCAYAAN DAN LOYALITAS PELANGGAN PT. KERETA API INDONESIA (PERSERO) - Anni Yudiastuti; Cornelius Niwadolo (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to examine the effect of the company's qualityonline services (E-Servqual) on customer loyalty in PT KeretaApi Indonesia (Persero) with trust as an intervening variable,method of analysis using Partial Least Square (PLS). The results showed a direct effect and significant variable E-Servqual on the Trust (the Trust), where the value of t statistics for 5205 which is above ± 1.96 (5%). with coefficient of 0,488 positive path, can be interpreted that the better E-Servqual, would cause the Trust of consumers will also be higher. Path coefficient values indicate a direct and significanteffect of the variable Trust on loyality with a value of tstatistics for 9,005 which is above ± 1.96 (5%). From the pathcoefficient value of 0621 (positive), can be interpreted that thehigher the Trust (Trust) consumers, it will lead to customerloyalty will also be higher.